Impaired Cerebrovascular Reactivity in Huntington’s Disease - Chan, Suk Tak; Mercaldo, Nathaniel D.; Kwong, Kenneth K.; Hersch, Steven M.; Rosas, Herminia D. (Frontiers in Physiology, 2021)
There is increasing evidence that impairments of cerebrovascular function and/or abnormalities of the cerebral vasculature might contribute to early neuronal cell loss in Huntington’s disease (HD). Studies in both healthy individuals as well as in patients with other neurodegenerative disorders have used an exogenous carbon dioxide (CO2) challenge in conjunction with functional magnetic resonance imaging (fMRI) to assess regional cerebrovascular reactivity (CVR). In this study, we explored potential impairments of CVR in HD. Twelve gene expanded HD individuals, including both pre-symptomatic and early symptomatic HD and eleven healthy controls were administered a gas mixture targeting a 4-8mmHg increase in CO2 relative to the end-tidal partial pressure of CO2 (PETCO2) at rest. A Hilbert Transform analysis was used to compute the cross-correlation between the time series of regional BOLD signal changes (BOLD) and increased PETCO2, and to estimate the response delay of BOLD relative to PETCO2. After correcting for age, we found that the cross-correlation between the time series for regional BOLD and for PETCO2 was weaker in HD subjects than in controls in several subcortical white matter regions, including the corpus callosum, subcortical white matter adjacent to rostral and caudal anterior cingulate, rostral and caudal middle frontal, insular, middle temporal, and posterior cingulate areas. In addition, greater volume of dilated perivascular space (PVS) was observed to overlap, primarily along the periphery, with the areas that showed greater BOLD response delay. Our preliminary findings support that alterations in cerebrovascular function occur in HD and may be an important, not as yet considered, contributor to early neuropathology in HD.